Análise dos sistemas de produção dos estabelecimentos rurais do município de Palmital/SP em busca de estratégias para o desenvolvimento rural - Bianchi, Vinícius Rafael [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aimed to make an analysis of agrarian systems of the city of Palmital / SP, located in the center west region of São Paulo, more precisely in the Middle Paranapanema, through a historical context, landscape analysis and of existing studies on it. Then it was established the typology of farmers of the municipality and of production systems by them. Such an approach is based on a systemic approach, guided the premises of the diagnosis of agrarian systems tool. Defined typologies, the different forms of income generation of productive systems in that locality were established. Assuming the importance of equity in the maintenance and reproduction of agricultural production systems by means of multivariate statistical analysis (multiple regression model) were analyzed what are the factors that interfere positively or negatively in the agricultural income of farmers. Data collection for analysis was done through a survey form applied to a stratified sample of farmers, proportional (to the condition of the farm). All data collected are between the period August 2013 to July 2014. These results point allowed the transformation of agrarian systems of the study area and the presence of different types of farmers: employers and family, with diversification in these production systems, respectively; in cases in which it showed those factors that influence the result obtained in agricultural income positive or negative way. Anyway, enabling elaborate proposals for rural development to the city of Palmital / SP.

Este estudo teve como principal objetivo fazer uma análise dos sistemas agrários do município de Palmital/SP, localizado na região centro oeste do estado de São Paulo, mais precisamente na região do Médio Paranapanema, por meio de uma contextualização histórica, da análise da paisagem e dos estudos existentes sobre este município. Em seguida se estabeleceu a tipologia dos produtores rurais de Palmital/SP e dos sistemas de produção por eles praticados. Tal abordagem está baseada em um enfoque sistêmico, pautadas nas premissas da ferramenta do diagnóstico de sistemas agrários. Definidas as tipologias, foram estabelecidas as distintas formas de geração de renda daqueles sistemas produtivos na referida localidade. Assumindo a importância da variável renda na manutenção e reprodução dos sistemas de produção agrícola, por meio de análise estatística multivariada (modelo de regressão múltiplo) foram identificados quais são os fatores que interferem positiva ou negativamente na renda agrícola dos produtores rurais. A coleta dos dados para análise foi feita por meio de um formulário de pesquisa aplicado a uma amostra de produtores rurais estratificada, proporcional à condição do estabelecimento rural. Todos os dados coletados estão compreendidos entre o período de agosto de 2013 a julho de 2014. Os resultados deste trabalho permitiram apontar as transformações dos sistemas agrários da região estudada bem como a presença de distintos tipos dos produtores rurais: patronais e familiares, com diversificação nos sistemas produtivos destes, respectivamente, e com casos em que se evidenciaram aqueles fatores que influenciavam no resultado obtido na renda agrícola de maneira positiva ou negativamente. Enfim, possibilitando elaborar propostas de desenvolvimento rural ao município de Palmital/SP.
Analysis of production systems of rural establishments in the city of Palmital / SP in search of strategies for rural development
Keywords: Agrarian systems; Family farming; Statistical analysis; Agricultural income; Systemic approach; Sistemas agrários; Agricultura familiar; Análise estatística; Renda agrícola; Enfoque sistêmico